PENGEMBANGAN MULTIMEDIA BERBASIS WEB MUATAN IPA SISWA KELAS V DI SEKOLAH DASAR - Yeni Eliza Ferawati; Murjainah; Sylvia Lara Syaflin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes a product in the form of web-based multimedia in natural science learning subjects for fifth-grade elementary school students. The research method used is research and development with the Hannafin and Peck model, which consists of three stages; 1) the need for assessment, 2) the design, and 3) the development and implementation stage. The research subjects involved fifth-grade students at SDN 35 Palembang. Data collection techniques used were unstructured interviews, questionnaires, tests, and documentation. Data analysis was the validity analysis, practicality, and potential effects. The study indicated applying web-based multimedia was valid with a score of 89.2% in the